Eksplorasi Pengaruh Pembelajaran Kooperatif terhadap Motivasi Internal Siswa Sekolah Dasar Kelas III - Tika Tri Yuni Absari; Mir’ah Zahra Rifadni; Rahmat Dhani; Agung Setyawan (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study explores the influence of cooperative learning on third-grade elementary students’ intrinsic motivation. Adopting a descriptive mixed-methods design, data were gathered via a Likert-scale intrinsic-motivation survey (N = 24) and a semi-structured interview with the classroom teacher. Observed indicators included persistence after failure, curiosity, pride in accomplishment, preference for collaboration, and comfort in voicing ideas. Findings indicate that most students exhibit relatively high intrinsic motivation—particularly in persistence and pride—alongside positive attitudes toward group work. While cooperative lessons increased visible participation, their advantage over other instructional methods was limited. The primary challenge was heterogeneous literacy skills (reading–writing), which left some students passive or sidelined during group tasks, whereas higher-achieving peers tended to dominate. Practical implications highlight the need for tiered task differentiation, clear and rotating group roles, peer tutoring, literacy scaffolding (mini-lessons and illustrated glossaries), individual accountability, and process-focused feedback. The study concludes that cooperative learning can strengthen intrinsic motivation, but requires literacy support and inclusive role design to achieve broad and equitable impact.